Evolution - Futuyma, Douglas J (Sunderland : Sinauer Associates, 2013)
Thoroughly updated with new content, figures and citations, the third edition addresses major themes in contemporary evolutionary biology - including the history of evolution, evolutionary processes, adaptation, and evolution as an explanatory framework - at levels of biological organization ranging from genomes to ecological communities.
Glossary G-1-14p.; Literature cited LC-1-37p.; Illustration credits IC-1-2p.; Index I-1-36p.
Keywords: Genes; Speciation; Species; Phenotypic